answersLogoWhite

0

What is the rule for 1 2 6 24?

Updated: 9/23/2023
User Avatar

Wiki User

10y ago

Best Answer

There are infinitely many possible answers.

One such is Un = (11n3 - 57n2 + 100n - 48)/6 for n = 1, 2, 3, ...

A more likely one though, is Un = n! = n*(n-1)*...*2*1

There are infinitely many possible answers.

One such is Un = (11n3 - 57n2 + 100n - 48)/6 for n = 1, 2, 3, ...

A more likely one though, is Un = n! = n*(n-1)*...*2*1

There are infinitely many possible answers.

One such is Un = (11n3 - 57n2 + 100n - 48)/6 for n = 1, 2, 3, ...

A more likely one though, is Un = n! = n*(n-1)*...*2*1

There are infinitely many possible answers.

One such is Un = (11n3 - 57n2 + 100n - 48)/6 for n = 1, 2, 3, ...

A more likely one though, is Un = n! = n*(n-1)*...*2*1

User Avatar

Wiki User

10y ago
This answer is:
User Avatar
More answers
User Avatar

Wiki User

10y ago

There are infinitely many possible answers.

One such is Un = (11n3 - 57n2 + 100n - 48)/6 for n = 1, 2, 3, ...

A more likely one though, is Un = n! = n*(n-1)*...*2*1

This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What is the rule for 1 2 6 24?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is the rule for the sequence of 6 12 18 24?

t(n) = 6*n where n = 1, 2, 3, etc


What is the rule for 6 23 1 24?

One possible answer: Un = (28n3 - 207n2 + 459n - 268)/2 for n = 1, 2, 3, ...


What is the rule of 12 6 3 1.5?

t(n) = 24/2n, n = 1, 2, 3, ...


What is the rule to this pattern 1 6 21 56 126?

t(n) = (5n4 - 10n3 + 55n2 - 50n + 24)/24 where n = 1, 2, 3, ...


What is the rule for 6 18 24 30?

ni = ni-1+6


How do you make 24 out of 1 2 6 7?

(7 + 1) × 6 ÷ 2 = 24.


Who to make 24 with 2 6 1 3?

2*6*(-1+3) = 24


How can you make 24 with 2 9 6 and 1?

(2*9)+(6*1)=24


How do you make 24 with 9 6 1 2?

(9 - 1) * 6 / 2 = 24.


What is 2 and 6 over 8 minus 5 over 6?

2 6/8 - 5/6 = 2 18/24 - 20/24 = 1 24/24 + 18/24 = 1 42/24 - 20/24 = 1 22/24 or 1 11/12


How can you get 6 5 2 and 1 to equal 24?

6 * [5-(2-1)] = 6*[5-1] = 6*4 = 24


How do you make 2 6 1 3 equal 24?

(2 + 6) * 1 * 3 = 24.